The Power of Homeownership: The case for Iowa Heartland Habitat for Humanity - Esha Jayswal; Joseph Ugrin; Disa Cornish; Brent Buhr; Ali Parrish (Journal of Public and Nonprofit Affairs)
This research examines the impact of financially assisted homeownership for Iowa Heartland Habitat for Humanity home recipients as measured in life satisfaction. We develop and assess a model with homeownership as the independent variable and financial well-being, current health, and psychological well-being as mediating variables that impact life satisfaction. We utilize data from 184 Iowa Heartland Habitat for Humanity homeowners and applicants to test the model. The findings show that homeownership through Iowa Heartland Habitat for Humanity is related to life satisfaction. That relationship is partially mediated by financial well-being, current health, and psychological well-being, where the mediating variables amplify the relationship between homeownership and life satisfaction.